Efektifitas Rebusan Daun Kelor (Moringa Oleifera) Terhadap Produksi ASI Pada Ibu Postpartum - Blegur, Maiyolisa Alvayona; Friscila, Ika; Rahmawati, Dwi; ., Noval (JIDAN Jurnal Ilmiah Bidan, 2024)
Background: Mother's milk is a source with a balanced composition for the baby's growth and development needs. In 2019 the coverage of exclusive breastfeeding at the Pekauman 1 Community Health Center (0.51%), in 2020 it was 22 (1.86%), and in 2021 it was 55 (4.79%). Exclusive breastfeeding coverage at the Pekauman Community Health Center is still below the target set by the Indonesian Ministry of Health, namely 80%. The high nutritional value content in Moringa leaves can be used to fulfill the nutritional needs of breastfeeding mothers. Objective: Determine the effectiveness of giving boiled Moringa leaves (Moringa oleifera) on breast milk production in postpartum mothers in the Pekauman Community Health Center working area. Method: Pre-experimental designs method with a one-group pretest-posttest design. The collection was carried out using purposive sampling with a sample of 10 female respondents at the Pekauman Community Health Center. Data analysis used the Wilcoxon Signed Rank Test. Results: Based on the results of research with a total of 10 respondents, based on age, there were 18-32 years old and respon. dents with education from elementary to high school. Before the intervention, 6 respondents (60%) experienced non-smooth breast milk production and 4 respondents (40%) experienced smooth milk production. Then after the intervention, respondents drank Moringa leaf decoction. The majority of respondents experienced smooth breast milk production, 9 people (90%) while only 1 person (10 %) who experience irregular breast milk production. Conclusion: There is an effectiveness of giving boiled water from Moringa oleifera leaves on breast milk production in breastfeeding mothers in the Pekauman Community Health Center working area in 2024 with p = 0.007.